Constitutionalization of criminal proceedings: concept and content - Rakhmetulin, A.D. (Bulletin of the Karaganda University “Law Series”, 2023)
The theoretical and practical significance of the topic of the constitutionalization of criminal proceedings is predetermined by the increasing influence and effect of constitutional ideas, principles and values in the legal regulation of public relations concerning legislation, as well as the pre-trial and judicial stages of criminal proceedings. First of all, constitutional values should be ensured in the sphere of legislative activity, so that cases when norms and provisions of criminal procedure legislation are recognized as inconsistent with the Constitution of the Republic of Kazakhstan are excluded, and in extreme cases reduced. In addition, effective measures are needed to ensure that all subjects of the application of the norms of criminal procedure legislation of the values and priorities proclaimed by the Constitution of the Republic of Kazakhstan, which leads to an adequate assessment of the fact that the highest values of the Republic of Kazakhstan are a person, his life, rights and freedoms. In this aspect, an important direction in the study of the phenomenon of constitutionalization is the scientific understanding of the question of what constitutes the constitutionalization of criminal proceedings, what is its relationship with the constitutionalization of the entire legal system, how these issues are considered by the scientific community, what measures are taken by various actors to ensure the constitu- tionalization of criminal procedure legislation. The article analyzes these issues taking into account the factthat there are very few scientific developments in Kazakhstan on this issue, and the concept of constitutionalization is studied within the definition of other terms and categories: constitutionalism, constitutional order and the rule of law. The author of the article considers the concept of constitutionalization of criminal proceedings through the content of the activities of various constitutionalization subjects.